Redução das emissões dos gases de efeito estufa na região do alto Paraguaçu com a ampliação do sistema elétrico de fonte hidráulica - Silva, Marilane de Sousa Miranda (2009)
This paper is based on the following objectives: to state that the increase in the supply of electric energy generated by hydroelectric sources in the Alto Paraguaçu Region, in the State of Bahia, will bring the possibility to replace partially the diesel driven motors used for water capture and irrigation producing effectively the greenhouse gas (GHG) emissions reduction and to demonstrate that it is a viable alternative to attend the Clean Development Mechanism (CDM). In order to reach theses objectives, the paper was developed as a case study including the 34 members of the Association of the Irrigators in the Alto Paraguaçu (AIAP). It was based on a documentary research of the primary and secondary data following by a proposal of the Project Concept Document (PCD) obtaining an estimated Greenhouse Gas (GHG) Emission reduction by 204.164 t CO2 in 10 years. Analyzing these results the paper concludes for the project viability related to Clean Development Mechanism (CDM).